Compressive Cervicothoracic Adhesive Arachnoiditis following Aneurysmal Subarachnoid Hemorrhage: A Case Report and Literature Review - Rahmathulla, Gazanfar; Kamian, Kambiz (Journal of Neurological Surgery Reports, 2014)
We present the case of a 55-year-old woman with diffuse adhesive arachnoiditis in the posterior fossa and cervicothoracic spine following posterior inferior cerebellar artery aneurysmal subarachnoid hemorrhage (SAH). She underwent aneurysm clipping with subsequent gradual neurologic decline associated with sensory disturbances, gait ataxia, and spastic paraparesis. Magnetic resonance imaging revealed diffuse adhesive arachnoiditis in the posterior fossa and cervicothoracic spine, syringobulbia, and multiple arachnoid cysts in the cervicothoracic spine along with syringohydromyelia. Early surgical intervention with microlysis of the adhesions and duraplasty at the clinically relevant levels resulted in clinical improvement. Although adhesive arachnoiditis, secondary arachnoid cysts, and cerebrospinal fluid flow abnormalities resulting in syrinx are rare following aneurysmal SAH, early recognition and appropriate intervention lead to good clinical outcomes.
Keywords: aneurysmal subarachnoid hemorrhage; adhesive arachnoiditis; arachnoid cysts; syringohydromyelia; syringobulbia